Efficacy and safety of colesevelam for the treatment of bile acid diarrhoea: a double-blind, randomised, placebo-controlled, phase 4 clinical trial. (April 2023) - Borup, Christian; Vinter-Jensen, Lars; Jørgensen, Søren Peter German; Wildt, Signe; Graff, Jesper; Gregersen, Tine; Zaremba, Anna; Borup Andersen, Trine; Nøjgaard, Camilla; Timm, Hans Bording; Rainteau, Dominique; Hansen, Svend Høime; et al.
Summary: Background: Bile acid diarrhoea is a common but overlooked cause of chronic watery diarrhoea. Plasma 7α-hydroxy-4-cholesten-3-one (C4) is an alternative to the gold standard tauroselcholic [ 75 Se] acid (SeHCAT) test. Low-certainty evidence supports sequestrant treatment, including colesevelam. We aimed to determine the efficacy and safety of colesevelam in bile acid diarrhoea. Methods: In this randomised, double-blind, placebo-controlled, investigator-initiated phase 4 trial of the sequestrant colesevelam in bile acid diarrhoea (SINBAD), we enrolled consecutive patients aged 18–79 years without inflammatory bowel disease attending SeHCAT testing for suspected bile acid diarrhoea at four Danish secondary care centres. Participants were randomly allocated 1:1 to receive 12 days of treatment with colesevelam (overencapsulated tablets of 625 mg) or placebo, with the starting dose of two capsules twice daily and titrated to effect during the first 5 days of treatment. A pharmacist independent of the clinical investigators generated a randomisation list on the web page randomization.com using block randomisation (randomisation was not stratified). C4 and SeHCAT diagnostic results were blinded during treatment. We treated all patients with diarrhoea, with a daily mean of 3·0 or more bowel movements or 1·0 or more watery bowel movements (Bristol stool scale type 6 and 7). Remission was defined as the absence of both these criteria during treatment days 6–12. The primary outcome was the intention-to-treat remission rate in bile acid diarrhoea diagnosed by C4 concentration greater than 46 ng/mL. A secondary outcome was the intention-to-treat remission rate in bile acid diarrhoea diagnosed by SeHCAT retention of 10% or less. This trial is registered with ClinicalTrials.gov, NCT03876717 . Findings: Between Oct 25, 2018, and July 1, 2021, 168 patients were randomly assigned to receive colesevelam (n=84) or placebo (n=84). 41 patients had C4 concentration greater than 46 ng/mL (22 assigned to the colesevelam group and 19 to the placebo group). For the C4-defined primary outcome, 14 (64%) of 22 participants receiving colesevelam versus three (16%) of 19 participants receiving placebo achieved remission (adjusted odds ratio 9·1, 95% CI 1·9–62·8; p=0·011). For the SeHCAT-defined secondary outcome, 75 of the 168 participants had retention of less than 10% (37 assigned to the colesevelam group and 38 assigned to the placebo group); 22 (59%) of 37 participants receiving colesevelam achieved remission versus five (13%) of 38 participants receiving placebo (adjusted odds ratio 11·1, 95% CI 3·4–45·6; p=0·00020). There were no serious adverse events. Common adverse events were transient. For patients receiving colesevelam within the primary outcome population, five had abdominal pain, nine had bloating, and four had nausea. For patients receiving placebo, four had abdominal pain, four had bloating, and one had nausea. No participants with bile acid diarrhoea withdrew due to adverse events. Interpretation: Colesevelam was superior to placebo at inducing remission of bile acid diarrhoea diagnosed with C4 concentration greater than 46 ng/mL. Secondary outcome data suggest similar efficacy treating SeHCAT-defined bile acid diarrhoea. Colesevelam was safe during the treatment. Funding: Fabrikant Vilhelm Pedersen og hustrus mindelegat; recommended by the Novo Nordisk Foundation.